Pathophysiological Considerations in Periorbital Necrotizing Fasciitis: A Case Report. (7th February 2023) - Hadizamani, Yalda; Anastasi, Stefano; Schori, Anouk; Lucas, Rudolf; Garweg, Justus G.; Hamacher, Jürg
ABSTRACT: Background: Periorbital necrotizing fasciitis (PNF) is a rare complication of bacterial infection, associated with irreversible inflammatory destruction of soft tissues like subcutaneous tissue and superficial fascia. PNF can cause visual loss, septic shock and death within hours to days. Since the infection progresses rapidly from a local disease to septic shock, prompt identification and decisive interventions are mandatory. Aim: Considering pathophysiology, differential diagnosis, and treatment options, we report a case of PNF and its outcome. Methods: A 69 years old male with febrile periorbital swelling had been diagnosed with bilateral PNF, caused by dual infection with Streptococcus pyogenes (S. pyogenes) and Staphylococcus aureus (S. aureus) based on conjunctival swabs. Results: The superantigens produced by S. pyogenes have been identified as key to the rapid dissemination of infection and severity of systemic manifestations. Conclusion: A combination of intravenous antibiotics and regular surgical debridements resulted in a beneficial outcome in our patient.